Foreign direct investment and technologial change - Cantwell, John (The globalization of the world economy, 1999)
This is a collection of the major writings to have appeared on foreign direct investment (FDI) and technological change since 1966. Its coverage includes: the early analysis of FDI and technology; and the theoretical foundations of the analysis of technological change in multinational firms.